The Role of Self-Esteem in Social Feedback: An fMRI Study - van der Miesen, Maite (Student Undergraduate Research E-journal!, 2015)
In this study we investigated the role of trait self-esteem in social feedback in 53 women, using questionnaires and functional magnetic resonance imaging (fMRI). Results showed that women with higher trait self-esteem did not feel worse after social feedback and showed brain activity during negative feedback in areas involved in emotion regulation. Women with lower trait self-esteem did feel worse after social feedback and showed more brain activity during positive feedback compared to negative and neutral feedback. We concluded that women with lower trait self-esteem display a preference for positive feedback and do not cope effectively with negative feedback.